The education of the teachers of English as a lingua franca: a transformative perspective - Sifakis, N. (International Journal of Applied Linguistics, 2007)
The article responds to the emerging need for a general framework for ELF (English as a lingua franca) teacher education that would appropriately inform and sensitize ESOL (English for speakers of other languages) practi-tioners about ELF teaching matters. The teacher education model put forward is based on the transformative framework for adult education suggested by Mezirow and has five phases. The framework aims at bringing about the much-needed paradigm shift in postmodern ESOL pedagogy by transform-ing ESOL teachers' worldviews about English and English language pedagogy and empowering them in bringing about the necessary changes in their own teaching context.